Perceptions and experiences of professional nurses of their role relating to clinical assessment of nursing students in a private hospital in Gauteng - Davis, Colleen Penelope (My University, 2021)
The assessment of the clinical competence of nursing students is necessary to determine if they have acquired the necessary competencies to be registered with the South African Nursing Council. Professional nurses working in the clinical environment are expected to assess students, but they have no educational background or specific training in assessment and are often overburdened with clinical responsibilities. The quality of assessment is poor with inaccurate and inconsistent results. As it is not possible to remove the responsibility of assessment from the professional nurses, it is essential to equip them with the required skills to fulfil this responsibility as effectively as possible. To do this, it is essential to firstly understand how the professional nurses perceive their role relating to assessment of students plus what experiences they have had in that role. The aim of the study was to understand the perceptions and explore the experiences of professional nurses of theirrole relating to clinical assessment of nursing students in a private hospital in South Africa.The study adopted a qualitative approach using an exploratory descriptive design. The population consistedof the professional nurses employed in the clinical areas responsible for the assessment of nursing students. The data was collected through semi-structured interviews and analysed using Braun and Clarke’s (2006)six steps of thematic analysis. The data showed that the participants in the research setting have a superficial understanding of the purpose of assessment. The participants perceive their role in the clinical assessment of nursing students to be that of a mentor to guide and support the students and their experiences reinforce this. They use the clinical assessment of nursing students to determine the overall capabilities of the nursing students but do not perceive their role as having to performand sign off clinical assessments of nursing students, using assessment tools, to provide proof of the attainment of clinical skills.
A research report submitted to the Faculty of Health Sciences, University of theWitwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing, 2021